18th Mediterranean Conference on Control and Automation, MED'10 2010
DOI: 10.1109/med.2010.5547822
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wind turbine LQG controllers using Individual Pitch Control to alleviate fatigue loads

Abstract: This paper focuses on the design of Linear Quadratic Gaussian (LQG) controllers for variable-speed horizontal axis Wind Turbines (WT). These turbines use blade pitch angle and electromagnetic torque control variables to meet specified objectives for Full Load (FL) zone. The main control objectives are to reduce structural dynamic loads and to regulate the power of the WT. The controllers are designed in order to optimize a trade-off between several control objectives. Four different LQG using Individual Pitch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 7 publications
(7 reference statements)
0
23
0
Order By: Relevance
“…Conversely Jureczko et al [12] demonstrated that pure aerodynamic optimization is insufficient when blades become longer than 45 m and the dynamic behavior becomes imperative, mainly because of the prominence of fatigue loads. Many studies attempted to reduce fatigue loads while generating sufficient power by dynamically controlling the blade pitch [7,[13][14][15][16][17][18]. Yet, additional restraints that aerodynamicist had and still have to consider are the public acceptance mainly from the generated noise by the wind turbine.…”
Section: Avoid Resonances and Blade/tower Collisionsmentioning
confidence: 99%
“…Conversely Jureczko et al [12] demonstrated that pure aerodynamic optimization is insufficient when blades become longer than 45 m and the dynamic behavior becomes imperative, mainly because of the prominence of fatigue loads. Many studies attempted to reduce fatigue loads while generating sufficient power by dynamically controlling the blade pitch [7,[13][14][15][16][17][18]. Yet, additional restraints that aerodynamicist had and still have to consider are the public acceptance mainly from the generated noise by the wind turbine.…”
Section: Avoid Resonances and Blade/tower Collisionsmentioning
confidence: 99%
“…with variables p(θ) ∈ R 3 for θ ∈ [0, 3 ]. In the model given by equations (1)- (4), τ x only depends on p(θ) through the lift and drag coefficients C l (α) and C d (α), an example of which are illustrated in figure 4 [8].…”
Section: A Power Maximizationmentioning
confidence: 99%
“…These costs are significant, and dramatically impact the profitability of the turbine. Many studies [1], [2], [3], [4], [5] have been performed which attempt to reduce fatigue loads while also generating sufficient power by dynamically controlling blade pitching. In this paper, we present a general blade pitching approach for fatigue load minimization based on convex optimization.…”
Section: Introductionmentioning
confidence: 99%
“…That type of control shows useful properties of good performance and robustness in controller design applied to wind energy converters system [1]. Although the application of LQG control for DFIG wind turbines is not new, recent research report using LQG controllers successfully [2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%